2020
DOI: 10.21203/rs.3.rs-88566/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uterine prolapse and associated factors among reproductive age women in Dawro zone, southwest Ethiopia: a community based cross sectional study

Abstract: Background: Uterine Prolapse is an important but one of the most neglected public health problems causing maternal morbidity and mortality among women of reproductive age in developing countries including Ethiopia. However, yet few data are available with respect to uterine prolapse. The objective of this study was to assess the prevalence of, and factors associated with uterine prolapse among women of reproductive age.Methods: A community based cross-sectional study was conducted in Loma Woreda, Dawro southwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…The prevalence of POP in this study is higher than the report of studies done in Southwest Ethiopia (5.9%), 13 Nigeria (3.9%), 32 and Ghana (2.6%). 33 The discrepancy in the estimation of the prevalence of POP might be due to variations in sample size, study setting, and study participants.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The prevalence of POP in this study is higher than the report of studies done in Southwest Ethiopia (5.9%), 13 Nigeria (3.9%), 32 and Ghana (2.6%). 33 The discrepancy in the estimation of the prevalence of POP might be due to variations in sample size, study setting, and study participants.…”
Section: Discussioncontrasting
confidence: 81%
“…12 It causes a variety of physical disabilities, such as the inability to work, difficulty in walking or standing up, peeing or defecating, painful intercourse, increasing social stigma, and economic destitution. 13 POP mostly affects women between the ages of 50 and 70 years, many women spend a significant portion of their lives dealing with its effects as it became a more serious issue as women's life expectancies have been increasing, and it is anticipated to double in the next 25 years. 2,14 The report of studies done across the world has identified risk factors for the development of POP such as obesity, 2 age at last birth, [15][16][17] parity, 15,18 gravidity, 15 mode of delivery, 19 delivery by unskilled birth attendants, 16,18 family history of POP, 18 prolonged labor, 17 educational status, 18 occupational status, 15,18 genetic factors, anemia, 17 body mass index, 18 and carrying heavy objects.…”
Section: Introductionmentioning
confidence: 99%
“…In the Southern Nation Nationality and Peoples Region of Ethiopia, there were high burdens of pelvic organ prolapse, and the most common cause was old age, long hours of carrying heavy objects, a high parity, a history of home delivery, a history of chronic constipation, and a history of chronic cough (12,13) Pelvic organ prolapse is a signi cant public health issue that affects the lives of millions of women (14). On average, POP in uenced 19.7% of women in developing countries (15).…”
Section: Introductionmentioning
confidence: 99%
“…It is the leading indication for hysterectomy in postmenopausal women and accounts for 15-18% of procedures in all age groups [5]. In the Southern Nation Nationality and Peoples Region of Ethiopia, there were high burdens of pelvic organ prolapse, and the most common cause was old age, long hours of carrying heavy objects, a high parity, a history of home delivery, a history of chronic constipation, and a history of chronic cough [6,7].…”
Section: Introductionmentioning
confidence: 99%